A randomized study of pomalidomide vs placebo in persons with myeloproliferative neoplasm-associated myelofibrosis and RBC-transfusion dependence - Tefferi, A; Al-Ali, H K; Barosi, G; Devos, T; Gisslinger, H; Jiang, Q; Kiladjian, J-J; Mesa, R; Passamonti, F; Ribrag, V; Schiller, G; Vannucchi, A M; et al. (Leukemia, 2017)
RBC-transfusion dependence is common in persons with myeloproliferative neoplasm (MPN)-associated myelofibrosis. The objective of this study was to determine the rates of RBC-transfusion independence after therapy with pomalidomide vs placebo in persons with MPN-associated myelofibrosis and RBC-transfusion dependence. Two hundred and fifty-two subjects (intent-to-treat (ITT) population) including 229 subjects confirmed by central review (modified ITT population) were randomly assigned (2:1) to pomalidomide or placebo. Trialists and subjects were blinded to treatment allocation. Primary end point was proportion of subjects achieving RBC-transfusion independence within 6 months. One hundred and fifty-two subjects received pomalidomide and 77 placebo. Response rates were 16% (95% confidence interval (CI), 11, 23%) vs 16% (8, 26%; P =0.87). Response in the pomalidomide cohort was associated with ⩽4 U RBC/28 days (odds ratio (OR)=3.1; 0.9, 11.1), age ⩽65 (OR=2.3; 0.9, 5.5) and type of MPN-associated myelofibrosis (OR=2.6; 0.7, 9.5). Responses in the placebo cohort were associated with ⩽4 U RBC/28 days (OR=8.6; 0.9, 82.3), white blood cell at randomization >25 × 10 9 /l (OR=4.9; 0.8, 28.9) and interval from diagnosis to randomization >2 years (OR=4.9; 1.1, 21.9). Pomalidomide was associated with increased rates of oedema and neutropenia but these adverse effects were manageable. Pomalidomide and placebo had similar RBC-transfusion-independence response rates in persons with MPN-associated RBC-transfusion dependence.